Constructing Decolonial Pedagogies: Local Responses to Gender Issues in Kerala’s English Textbooks - Lekshmi, R. (University of Jaffna, 2025)
From the time of the state formation, Kerala was one of the few states in India willing to promote English learning from the early years of schooling. This has also meant that colonial loyalties remain deep-rooted in the Keralan subconscious and, more evidently so in the pedagogical practices. With an awareness of neocolonial power structures that exclude the experiences of different members of the gender spectrum and question their national belonging, the Kerala education department has formulated some macro level responses to gender issues in the last few years. While recognizing the importance of socialization in gender discrimination, there were initiatives to promote gender-friendliness in the school infrastructure. In 2022, a committee was set up to include sexuality education in the school curriculum. Some government schools stood out for the unique initiative of introducing the gender-neutral address of ‘teacher’ instead of ‘sir’/ ‘madam’ in the school. However, recent literature has shown that the imposition of gender neutrality fails to address the nuances of the gendered classroom realities. Due to opposition from religious groups in 2022, the state government had to clarify that there was no move to impose gender-neutral uniforms in schools and instead, it could be adopted as per the discretion of the institution. The publishing of the new draft Kerala Curriculum Framework (KCF) in 2023 led to the gender auditing of the curriculum and textbooks to ensure that no content, picturization, language or behavior enables gender discrimination. The revised textbooks of Classes 1,3,5,7 and 9 were lauded for their gender inclusive representations. This study employs critical discourse analysis to qualitatively examine the five new Kerala English Readers used for Classes 1,3,5,7 and 9 to understand whether the gender roles depicted can constitute counter practices to the neocolonial pedagogies that perpetuate hierarchies in the English classrooms of Kerala. Following H. Song’s framework, the content analysis looks at cultural representations of gender in the texts, images, exercises, dialogues, and captions and the data will be interpreted in three levels of superficial interactions, hybridization and critical reflections. The analysis of the textbook revisions also finds out whether the seven types of gender bias as identified by previous studies namely invisibility, stereotyping, imbalance, unreality, fragmentation, linguistic bias and cosmetic bias in the curriculum are effectively combated. This reveals the potential of these representations to initiate critical reflections on gender while pointing at challenges that need to be addressed through culturally sensitive gender-inclusive practices in the classrooms. In the contexts of the National Education Policy 2020 and the National Curricular Framework 2023 which aim to transform the educational experience by reclaiming Indian knowledge systems and local learning resources, the study has future implications in evaluating how language education policies can challenge gender discrimination through decolonial pedagogies that value diverse belief systems, practices, and knowledges in the linguistic and socio political realities of each state in India.
Keywords: English textbooks; Cultural representations; Decolonial pedagogies; Gender discrimination